A theory-based hand hygiene educational intervention for enhancing proper handwashing behaviour among school children in the Ejisu-Juaben Municipality of Ghana - Appiah-Brempong, Emmanuel (KNUST, 2025)
A thesis submitted to the department of health promotion & education, school of public health, college of health sciences in fulfilment of the requirements for the Degree of Doctor of Philosophy in Public Health